Facile Synthesis of Ultrahigh‐Surface‐Area Hollow Carbon Nanospheres and their Application in Lithium‐Sulfur Batteries. Issue 8 (9th January 2018) - Zeng, Shao‐Zhong; Yao, Yuechao; Huang, Lin; Wu, Hongliang; Peng, Biaolin; Zhang, Qi; Li, Xiaohua; Yu, Liang; Liu, Shiyu; Tu, Wenxuan; Lan, Tongbin; Zeng, Xierong; et al.
Abstract: Hollow carbon nanospheres (HCNs) with specific surface areas up to 2949 m 2  g −1 and pore volume up to 2.9 cm 3  g −1 were successfully synthesized from polyaniline‐co‐polypyrrole hollow nanospheres by carbonization and CO2 activation. The cavity diameter and wall thickness of HCNs can be easily controlled by activation time. Owing to their large inner cavity and enclosed structure, HCNs are desirable carriers for encapsulating sulfur. To better understand the effects of pore characteristics and sulfur contents on the performances of lithium‐sulfur batteries, three composites of HCNs and sulfur are prepared and studied in detail. The composites of HCNs with moderate specific surface areas and suitable sulfur content present a better performance. The first discharge capacity of this composite reaches 1401 mAh g −1 at 0.2 C. Even after 200 cycles, the discharge capacity remains at 626 mAh g −1 . Abstract : Hollow carbon nanospheres (HCNs) with specific surface areas up to 2949 m 2  g ‐1 and pore volume up to 2.9 cm 3  g ‐1 were successfully synthesized from polyaniline‐co‐polypyrrole hollow nanospheres by carbonization and CO2 activation. Owing to their large inner cavity and enclosed structure, HCNs are desirable carriers for encapsulating sulfur.